Facing the New Millenium: The 30th NU Congress at the End of the 20th Century - Hasyim, Syafiq; Darmadi, Dadi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2000)
Nahdlatul Ulama (NU), the Indonesian largest traditionalist Muslim organization with more than 30 million followers nationwide, faced the challenge of the new millennium by successfully bolding its 30th congress (muktamar) at Pesantren Lirboyo in Kediri, East Java. Approximately one million Nahdliyyins, as NU followers, are called to have enjoyed one of NU's biggest event cultural and ceremonial events for five day from November 22nd until November 27th 1999. The majority of participants came from Java, but many others came from as far away as Sumatera, Sulawesi, Kalimantan and Maluku.DOI: 10.15408/sdi.v7i1.721